Strategic Alliances and Technology in Tourism / Jaloni Pansiri and Jerry Courvisanos - Pansiri, Jaloni; Courvisanos, Jerry (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2011)
The purpose of this paper is to examine the role of strategic alliances in developing technology-based knowledge. In doing so, the study further links assessment of strategic alliance outcomes (technology benefits) to tourism executives' risk taking behaviour. A survey of Australian travel sector businesses was carried out and the results indicate that strategic alliances in tourism contribute marginally to technology-based knowledge. The study further found that executives in the travel sector of tourism are risk averse and this has tremendous implications for the choice of alliances they make and their perceptions with regard to the contribution of these alliances to technology-based knowledge. The findings of this paper imply that Australian industry policy needs to encourage strategic alliances that have the potential to stimulate knowledge based innovation.